CORRECTION OF ANISOMETROPIA BY PHAKIC INTRAOCULAR LENSES IN PATIENTS WITH CONGENITAL MYOPIA (World Bulletin of Public Health, 2024)
Refractive errors occupy a leading place among the causes of visual disorders in children and adolescents. Congenital ametropia — myopia, hypermetropia and astigmatism play a negative role in the formation of visual functions, often leading to gross forms of refractive amblyopia in children. Congenital myopia belongs to a separate group of refractive errors, which differs from acquired myopia in a number of ways. Goal. Analysis of the results of correction of anisometropia in high-grade congenital myopia in children by implantation of phakic introocular posterior chamber lenses (ICL). Methods. This study was conducted in the eye center of LLC "A.A.Yusupov". Operations were performed on 18 patients, including 10 boys and 8 girls, aged from 14 to 18 years. The observation period is from 1 year to 3 years. The initial spherical refraction was determined in the range from -9.0 to -18.0 D. Results. After surgery, visual acuity in all patients was 0,3 and higher. The spherical component of postoperative refraction averages -0.49 D. The average IOP value after surgery was 17 mm Hg. The loss of endothelial cells did not exceed 1.5% (from 0.5 to 1.5%). Conclusion. Correction of high-grade unilateral myopia in children by implantation of phakic posterior chamber lenses ICL leads to satisfactory results in terms of its effectiveness, predictability, stability and safety.